You Can Teach Every Patient: A Health Literacy and Clear Communication Curriculum for Pediatric Clerkship Students - Emily Spengler; Miriam Schechter; Paulo Pina; Hai Jung Helen Rhim (Association of American Medical Colleges, 2021)
Introduction Poor health literacy has a negative impact on various health care outcomes. Medical schools are not consistently providing health literacy training; when they do, they overly rely on didactics. Methods Our curriculum for third-year pediatric clerkship students taught principles of health literacy and evidence-supported clear communication strategies. Communication skills were structured on a novel mnemonic: CTEP (clear language, teach-back, effectively encouraging questions, and pictures). The curriculum included a 30-minute didactic, followed 1-2 weeks later by a 90-minute interactive workshop. All 188 clerkship students attended the didactic lecture; approximately half (90) attended the follow-up workshop. All students completed a formative objective structured clinical encounter. Standardized patients then evaluated students' use of the four clear communication skills. Students completed a survey to assess confidence, knowledge, and use of the skills. Results Compared to the didactic-only group, students in the didactic + workshop group more frequently used teach-back (53% vs. 27%, p < .01) and pictures (46% vs. 10%, p < .01). In addition, the didactic + workshop group had improved recall, self-reported use, and comfort with the skills. The didactic + workshop group solicited questions from the standardized patient less often, and there was no difference in use of clear language between the two groups. Discussion An interactive curriculum in health literacy and clear communication for pediatric clerkship students was superior to a didactic alone. Optimizing instructional methods for health literacy skills can help future physicians properly communicate with their patients to improve health outcomes.